Virus chimeras for gene therapy, vaccination, and oncolysis: adenoviruses and beyond - Kaufmann, Johanna K.; Nettelbeck, Dirk M. (Trends in molecular medicine, 2012)
Several challenges need to be addressed when developing viruses for clinical applications in gene therapy, vaccination, or viral oncolysis, including specific and efficient target cell transduction, virus delivery via the blood stream, and evasion of pre-existing immunity. With rising frequency, these goals are tackled by generating chimeric viruses containing nucleic acid fragments or proteins from two or more different viruses, thus combining different beneficial features of the parental viruses. These chimeras have boosted the development of virus-based treatment regimens for major inherited and acquired diseases, including cancer. Using adenoviruses as the paradigm and prominent examples from other virus families, we review the technological and functional advances in therapeutic virus chimera development and recent successful applications that can pave the way for future therapies.
Gesehen am 19.07.2018